(untitled) (Journal of Hama University, 2022)
This study was carried to investigate the effect of adding of thymus and rosemary powder to broiler standard diet, and alcoholic extract of both planets on some productive performance. 188 one-day old Ross strain unsexed chicks were randomly distributed into seen groups (26 chicks for each), as flowing: First group is control without any addition, second and third groups included the addition of 1 g thymus powder/kg diet and 1 g rosemary powder/kg diet respectively, and the fourth group included the addition of mixture of one-gram thymus and one-gram rosemary powder/kg diet. Fifth and sixth groups, the addition of 1 ml thymus alcoholic extract /L drinking water and 1 ml rosemary alcoholic extract /L drinking water respectively, and the seventh group included the addition of mixture of one ml thymus alcoholic extract and one ml rosemary alcoholic extract /L drinking water. The results showed significantly (P<0.05) positive effect of thymus and rosemary powder and extract on the average of body weight compared with control group at end of experiment (36 days). The results also showed that there was no significant effect (p>0.05) of adding the studied plant powder on the average weight of the heart muscle, lungs, and the legs. The two plants had a significant effect (p<0.05) on the average weight of the liver and muscular stomach (for rosemary powder only). Adding the alcoholic extract of the plant had a significant effect on the average weight of the internal organs, as there was a decrease in the average weight of the liver, muscular stomach, and the average weight of lungs and legs when adding thyme extract, while there was no significant effect on the average weight of the heart, lungs and legs when Add rosemary extract and a mixture of the two plants extract.